Pediatric Rhinosinusitis: Its Predisposing Factors and Management - Sethu Thakachy Subha (European Journal of Rhinology and Allergy)
Objective: Rhinosinusitis is a prevalent disease in children that can cause many substantial physical symptoms and have a detrimental infuence on their quality of life. This study aims to evaluate the predisposing factors, and management of pediatric rhinosinusitis patients.